Strategy for Implementing Digital Marketing (Case Study of a Coconut Fruit Expedition Business in Makassar City) - Syam, Agus; R, Raflianto; Isma, Andhika (PT. EQUATOR SINAR AKADEMIA, 2024)
This research aims to determine effective strategies for implementing digital marketing in running a coconut fruit expedition business in Makassar City. The research method used is descriptive qualitative research using data collection methods through observation, interviews and documentation of research objects which are then developed using Research and Development. The research results show that the implementation carried out by researchers for the Coconut Fruit Expedition in Makassar City with Research and Development implementing Digital Marketing such as WEBsite, Instagram, Facebook is important to implement because after planning and implementation using Research and Development it can be stated that digital marketing is very helpful for the expedition and consumers because it can make it easier to get information, communicate and transact online so that in this case it can prevent problems that exist in the 4.0 era and can meet consumer needs.